IMPLIKASI KONSTITUSIONAL LARANGAN RANGKAP JABATAN WAKIL MENTERI PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 128/PUU-XXIII/2025: Constitutional Implications of the Prohibition on Concurrent Positions Held by Deputy Ministers Following Constitutional Court Decision Number 128/PUU-XXIII/2025 - Irsyan Nugraha Zabidi; Ali Rido (Faculty of Law, Universitas Trisakti, 2026)
Constitutional Court Decision No. 128/PUU-XXIII/2025 reinforces the prohibition on dual positions for Deputy Ministers as a measure to safeguard integrity, prevent conflicts of interest, and ensure that their performance remains focused on core ministerial duties. This paper examines the Court’s legal reasoning and the effectiveness of the decision’s implementation within the Merah Putih Cabinet. The findings show that although the ruling provides clear normative boundaries, its implementation has not been fully effective. Several Deputy Ministers continue to hold concurrent positions as commissioners or officials in state-funded institutions, creating accountability issues and reflecting the strong influence of political accommodation in public office appointments. It is concluded that while the decision plays a significant role in structuring the position of Deputy Ministers. The legal issue addressed in this study is How does the implementation of Constitutional Court Decision Number 128/PUU-XXIII/2025 affect the practice of holding concurrent positions by Vice Ministers within the structure of the Merah Putih Cabinet for the 2024-2029 period